Fostering children's creative thinking skills with the 5-I training program. (June 2019) - Gu, Xiaojing; Dijksterhuis, Ap; Ritter, Simone M.
Highlights: We developed a single session, 2 -h creativity training program for children aged 7–12, called the 5-I training program. We scientifically examined the effectiveness of the training program using three widely used creativity tasks. Results showed that children's creative performance significantly improved from pre-measures to post-measures. The current findings demonstrate the effectiveness of the 5-I training program in fostering children's creative thinking skills. Abstract: Creative thinking is an important 21st century skill. To prepare children for our complex and fast-changing world, it is essential to cultivate their creative thinking skills. The objective of the current study was to develop and examine the effectiveness of a brief, domain-unspecific creativity training program: the 5-I training program. Children ( N = 172) aged 7–12 years participated in the training, which consisted of eight creativity exercises performed in a training session of two hours. The effectiveness of the training on stimulating children's creative thinking skills was assessed by means of a pretest and posttest comparison using three creativity tasks (Alternative Uses Task, drawing task and guessing task). For each task several measures of creative performance were examined (e.g., fluency, flexibility, infrequency, elaboration). Following the creativity training, improvements were observed on the three creativity tasks. The effectiveness of the 5-I training program was found for all measures of creative performance, except for flexibility. Implications for educational settings are discussed.